2016
DOI: 10.1002/adom.201500707
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Molybdenum Disulfide Nanoribbons with High Optical Anisotropy

Abstract: Two-dimensional Molybdenum Disulfide (MoS2) has shown promising prospects for the next generation electronics and optoelectronics devices. The monolayer MoS2 can be patterned into quasi-one-dimensional anisotropic MoS2 nanoribbons (MNRs), in which theoretical calculations have predicted novel properties. However, little work has been carried out in the experimental exploration of MNRs with a width of less than 20 nm where the geometrical confinement can lead to interesting phenomenon. Here, we prepared MNRs wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 52 publications
9
79
0
Order By: Relevance
“…Recently, Wu et al have demonstrated that MoS 2 nanoribbons demonstrate highly anisotropic optical behavior. The optical anisotropy and enhanced intensity of the Raman modes are attributed to anisotropy in optical absorption depending upon NR orientation and NR edges, which breaks up the translational symmetry of the crystal and relax selection rules, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wu et al have demonstrated that MoS 2 nanoribbons demonstrate highly anisotropic optical behavior. The optical anisotropy and enhanced intensity of the Raman modes are attributed to anisotropy in optical absorption depending upon NR orientation and NR edges, which breaks up the translational symmetry of the crystal and relax selection rules, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The HIM has shown potential to pattern and selectively introduce defects with high resolution into 2D materials such as MoS 2 , MoSe 2 , WSe 2 , and graphene . Of particular interest, transition metal dichalcogenide (TMD) nanoribbons have been theorized to exhibit unique properties depending upon edge termination .…”
Section: Introductionmentioning
confidence: 99%
“…Symmetry‐reduction as a method of disordering atoms to change the density of states in a certain direction by heterostructure enhances the dichroic ratio. Therefore, symmetry‐reduction as a valid method of enhancing structural anisotropy can numerously enrich the family of in‐plane anisotropy semiconductors and has extensively utilized in polarization‐sensitive photodetection …”
Section: Introductionmentioning
confidence: 99%
“…Besides, the active area patterned by these conventional methods is insufficient to be practically employed. To date, several alternative nanofabrication techniques have been reported, which relies on the following four methods: (1) selective growth on the patterned templates, 12,13 (2) reactive ion etching using patterned masks, 14,15 (3) direct removal by scanning lasers or ions, 16,17 and (4) peeling, transfer, and filling methods by controlling a surface adhesion energy. [18][19][20] In method (1), the prepared Mo nanowires were converted to MoS 2 nanowires through pyrolysis in H 2 S ambient; however, these MoS 2 nanowires exhibited unstable electrical properties owing to a Y.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…4(c)]. The absolute PL intensity was slightly weakened in the MNR due to the reduced active area and the open edges, 17,26 but the two exciton peaks were clearly observed at 1.83 eV and 1.97 eV related to the K-point transition in the Brillouin zone. 1 By contrast, the reference MNR with residues or the photoresist-coated MoS 2 displayed broad peaks with fluctuating backgrounds, implying that application devices based on such platforms will produce unstable characteristics.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%